2021
DOI: 10.1021/acs.jpclett.0c03685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare Earth Elements at Amorphous ReAlO3/SrTiO3 (Re = La, Pr, Nd, Sm, Gd, and Tm) Heterointerfaces

Abstract: Although the amorphous two-dimensional electron gas (a-2DEG) of oxides provides new opportunities to explore nanoelectronic as well as quantum devices, the intrinsic effect of rare earth (Re = La, Pr, Nd, Sm, Gd, and Tm) elements at ReAlO 3 /SrTiO 3 heterointerfaces is still largely unknown and needs to be addressed systematically. Herein, we first propose that the ionization potential of Re elements is a critical factor for the 2DEG fabricated by chemical spin coating. Furthermore, the photoresponsive propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Other detailed results of surface morphology, thickness, and chemical composition of the films have been reported in a previous study. 32 Further, the transport properties of 2DEGs at heterointerfaces are measured. The temperature-dependent sheet resistances (R s ), carrier densities (n s ), and mobilities (μ) of the ReAO/STO heterointerfaces are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other detailed results of surface morphology, thickness, and chemical composition of the films have been reported in a previous study. 32 Further, the transport properties of 2DEGs at heterointerfaces are measured. The temperature-dependent sheet resistances (R s ), carrier densities (n s ), and mobilities (μ) of the ReAO/STO heterointerfaces are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Other ReAO/STO samples prepared under the same preparation conditions have the same morphology and structure. Other detailed results of surface morphology, thickness, and chemical composition of the films have been reported in a previous study …”
Section: Results and Discussionmentioning
confidence: 99%
“…The cubic unit cell parameter of the STO:Mn single crystal is 3.90663(3) Å. Refinement of the occupancies of the cationic and anionic positions in SrTiO 3 showed that the nearly ideal stoichiometry is observed only in the Sr 2+ sublattice [0.9989 (6)], while the Ti 4+ [0.967(3)] and oxygen [0.988 (9)] sublattices are characterized by the difference from the theoretical values. To determine the position of the Mn cation, during the first stage, we refined the SrTiO 3 structure and built a map of the residual electron density (Figure 1c).…”
mentioning
confidence: 97%
“…1,2 It is believed that zero-point quantum fluctuations preclude the condensation of the polar soft mode and a macroscopic ferroelectric state does not form down to the millikelvin range. 1,2 At the same time, the dielectric permittivity reaches ∼10 4 without significant dispersion in the microwave frequency range, 3 which is attractive for application in various types of tunable electronic devices, 4,5 nanotechnology, 6,7 and photocatalysis. 8,9 At ∼105−110 K, STO undergoes an antiferrodistortive transition to a nonferroelectric tetragonal phase formed by out-of-phase tilts of oxygen octahedra.…”
mentioning
confidence: 99%
See 1 more Smart Citation